O uso do território por agentes torrefadores de cafés especiais do sul de Minas Gerais - Coutinho, Daniel Mendes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work aims to analyze the use of the territory by producers/roasters agents, for the attainment of special coffees in the South of Minas Gerais territory. To this end, it has been used the productive spatial circuit, as well as the cooperation circles as categories of analysis, to understand the use of the territory by roasters agents territorialized in the South of Minas Gerais. Thus, it has been made literature review about these categories, as well as to for the coffee sector and for concepts such as territory, competitiveness and product differentiation. Also, there was collection of secondary data on the sector, in order to base the competitive environment that agents studied are inserted. It has been used as a basis for the definition of the population, the Brazil Specialty Coffee Association (BSCA) database, which featured 6 companies in the object-territory, of which 5 responded the set of questions. The studied agents are characterized as coffee producers, who have identified that, by the differentiation for specials coffees and by the diversification of activities for the roasting; they could expand their incomes and reduce their vulnerability front to the international market. These actions are a result of the coffee market deregulation in the 1990s, and are a part of the actions taken by agricultural producers that, primarily, sought to add value to their products in exportation and, subsequently, to diversify their activities with the roasting to the Brazilian domestic market. With these actions, it has been observed that the activities of the agents are territorialized and, to this end, it is necessary the 'activation of specific resources' inherent in the territory of the South of Minas Gerais. Thus, it becomes clear a relation of belonging and dependence of these agents with the territory, which results in the characterization of the products that are produced there, as materialization of the use of the territory as 'shelt

Este trabalho objetiva analisar o uso do território por agentes produtores/torrefadores, para a obtenção de cafés especiais no território do Sul de Minas Gerais. Para tal, faz-se uso do circuito espacial produtivo, bem como dos círculos de cooperação como categorias de análise. Assim, foi realizada revisão bibliográfica acerca dessas categorias, assim como para o setor cafeeiro e para conceitos como território, competitividade e diferenciação de produto. Também, houve coleta de dados secundários sobre o setor, como forma de embasar o ambiente competitivo que os agentes estudados estão inseridos. Utilizou-se, como base para a definição da população, o banco de dados da Brazil Specialty Coffee Association (BSCA), que apresenta 6 empresas no território objeto, das quais, 5 responderam o roteiro de perguntas. Os agentes estudados se caracterizam como produtores de café, que por meio da diferenciação para os cafés especiais e da diversificação das atividades para a torrefação, começaram a ampliar seus rendimentos, diminuindo sua vulnerabilidade frente ao mercado internacional. Essas ações são consequência da desregulamentação do mercado de café, na década de 1990, e fazem parte das ações adotadas pelos produtores agrícolas que, primeiramente, buscaram agregar valor a seus produtos na exportação e, posteriormente, diversificar suas atividades com a torrefação para o mercado interno brasileiro. Com essas ações, observa-se que as atividades dos agentes estão territorializadas e, para tal, é necessária a ativação de recursos específicos inerentes ao território do Sul de Minas Gerais. Assim, evidencia-se uma relação de pertencimento e dependência destes agentes com o território, o que resulta na caracterização dos produtos ali produzidos como materialização do uso do território como abrigo
Keywords: Economic geography; Geografia econômica; Cafe - Torrefação; Solos - Uso; Concorrência; Geografia urbana; Minas Gerais, Sul